CORTICOSTEROIDS - ASSETS AND LIABILITIES ON PERIODONTIUM - Harshita, Nadimpalli; Kamath, Deepa G; Swati, Swati (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Corticosteroids are chemically similar to endogenous cortisol and are used fundamentally as replacement therapy in patients with adrenal insufficiency, and used as anti-inflammatory agents. They are widely used in systemic diseases such as rheumatoid arthritis, asthma, and connective tissue disorders. In dentistry primarily these are used to decrease post-operative pain and edema in inflammatory diseases such as oral lichen planus, pemphigus, and recurrent aphthous stomatitis. This action is predominantly due to eicosanoid formation that inhibits phospholipase A2 activity. Corticosteroids can be supplemented either topically systemically or as inhalational therapy. Research suggests that local application of corticosteroids shows favorable effect on the periodontal ligament and possesses antiresorptive effect, but long-term systemic therapy is a risk for periodontal diseases which may provoke attachment loss and disruption of transseptal fibers. Oral manifestations are common with the use of inhaled steroids and are dependent on dose, frequency, duration, and inhaler use. It is commonly associated with ulceration of tongue, buccal mucosa, and occasionally on the gingiva due to xerostomia and immune suppression. It also causes a decrease in bone mineral density. This review explains about various effects of different types of corticosteroids on periodontium used in dentistry.